SISTEM INFORMASI PEMATANGSIANTAR DIRECTORY MENGGUNAKAN METODE BACKWARD CHAINING BERBASIS MOBILE - Novendra Adisaputra Sinaga (Politeknik Bisnis Indonesia, 2018)
This Research is designed for an information system in the form of expert system applications to present information on Pematangsiantar Directory. The purpose of this system is to help provide information about the city of Pematangsiantar as a whole to the residents of Pematangsiantar city in particular and the local and foreign tourists as well as prospective investors in general. The system presents information in the form of public service to the residents of Pematangsiantar city government and other newcomers as well as products and services are made and offered by the business and government. The analysis was done by determining the first goal, then do the searching to obtain the desired information. The design system uses backward chaining inference method to the implementation of the system using My-SQL database systems and programming languages of PHP and JQuery. The system is based on mobile, so it can be accessed using a mobile device